Immune alterations in subacute sclerosing panencephalitis reflect an incompetent response to eliminate the measles virus - BARIŞ, SAFA (PUBLIC LIBRARY SCIENCE, 2021)
In subacute sclerosing panencephalitis (SSPE) the persistence of measles virus (MeV) may be related to the altered immune response. In this study, cytokine responses of lymphocytes and monocytes were evaluated in SSPE compared to controls with non-inflammatory (NICON) and inflammatory (ICON) diseases. Patients with SSPE (n = 120), 78 patients with ICON and 63 patients with NICON were included in this study. Phenotypes of peripheral blood mononuclear cells (PBMC) have been analyzed by flow cytometry. CD3 and CD28, and S. aureus Cowan strain I (SAC) stimulated and unstimulated cells were cultured and IL-2, IL-10, IFN-gamma, IL-12p40, IL-12p70 and IL-23 were detected in supernatants by ELISA. MeV peptides were used for MeV-specific stimulation and IFN-gamma secretion of PBMC was measured by ELISPOT. Spontaneous and stimulated secretions of IL-10 were lower in SSPE compared to both control groups. T cell stimulation induced lower IFN-gamma production than ICON group, but higher IL-2 than NICON group in SSPE. Stimulated PBMC produced lower IL-12p70 in SSPE and had decreased CD46 on the cell surface, suggesting the interaction with the virus. IFN-gamma responses against MeV peptides were not prominent and similar to NICON patients. The immune response did not reveal an inflammatory activity to eliminate the virus in SSPE patients. Even IL-10 production was diminished implicating that the response is self-limited in controlling the disease.
Keywords: CEREBROSPINAL-FLUID; CELLULAR RECEPTOR; MOLECULE SLAM; BRAIN-LESIONS; T-CELLS; EXPRESSION; INTERLEUKIN-12; ACTIVATION; CDW150; IL-10